Post-eccentric flywheel underwater undulatory swimming potentiation in competitive swimmers - Crespo, E.; Ruiz-Navarro, J. J.; Cuenca-Fernández, F.; Arellano, R. (Journal of Human Kinetics, 2021)
Underwater undulatory swimming (UUS) influence s overall swimming performance, therefore swimmers should try to maximize it. This research aimed to: 1) assess the effects of an activation protocol based on post-activation performance enhancements upon UUS; and 2) evaluate the differences between males and females. Seventeen competitive swimmers (male = 10; female = 7) participated in a cross-sectional study designed to test performance in UUS at 10 m after a traditional swimming warm-up (TRA) and after adding to the TRA 4 maximal half-squat repetitions on an inertial flywheel device (PAPE). A speedometer and an electronic timing system were used to obtain kinematic variables such as time, frequency and ve locity at 10-m, which were processed with MATLAB ® . A paired sample t test was applied to determine the differences of the kinematic variables between the TRA and PAPE. An independent sample t test was used to determine the effects of the PAPE in males and females. Participants reduced the time to cover 10 m after PAPE compared to the TRA (males: 5.77 ± 0.44 to 5.64 ± 0.46; females 6.34 ± 0.80 to 6.09 ± 0.66; p < 0.05). In addition, trends towards improvements in UUS velocity were obtained for males and females. However, push-off velocity and frequency showed a different tendency between genders (p < 0.05). In conclusion, the warm-up including repetitions on the flywheel device improved UUS performance. Some differences were obtained between genders after PAPE. Further research should confirm if the benefits obtained after the eccentric overload would depend either on gender or on other components such as fiber type composition.